2022
DOI: 10.1111/1471-0307.12883
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal turbulent flow ultraviolet‐C (UV‐C) radiation processing for cheese whey‐brines purification

Abstract: The effect of ultraviolet C (UV-C) light technology on whey-brine inoculated with five different pathogens (or surrogates) was examined: Listeria innocua (NCTC 11288), Staphylococcus aureus (NCTC 6571), Bacillus cereus (NCTC 7464), Escherichia coli (NCTC 9001) and Salmonella enteritidis (NCTC6676). The most resistant microorganism was L. innocua, requiring a UV-C dosage of 320 J/L. The inactivation for the rest of the bacteria occurred at equal or less than 200 J/L dosage. The results from this study indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In whey from cheese production, the resistance of relevant microorganisms in food areas ( L. innocua, Staphylococcus aureus, Bacillus cereus, E. coli and Salmonella Enteritidis) to UV‐C treatment in turbulent flow was evaluated. It was found that L. innocua showed much greater resistance than the others, requiring a dose of 320 J/L for its inactivation, while the other pathogens were inactivated with doses equal to or less than 200 J/L (Neokleous et al ., 2022).…”
Section: Uv‐c Treatment Applied To Foodmentioning
confidence: 99%
“…In whey from cheese production, the resistance of relevant microorganisms in food areas ( L. innocua, Staphylococcus aureus, Bacillus cereus, E. coli and Salmonella Enteritidis) to UV‐C treatment in turbulent flow was evaluated. It was found that L. innocua showed much greater resistance than the others, requiring a dose of 320 J/L for its inactivation, while the other pathogens were inactivated with doses equal to or less than 200 J/L (Neokleous et al ., 2022).…”
Section: Uv‐c Treatment Applied To Foodmentioning
confidence: 99%